Verification of Sub-national Claim for 'TB-free' Status of Rajsamand District, Rajasthan, India-2020 - Kalika Gupta; Mitin Parmar; Kush Davda; Shivangi Davda; Pooja Soni; Ashok K. Bhardwaj; Bhavesh Modi; Rajendra Awate (Wolters Kluwer Medknow Publications, 2024)
Background: Tuberculosis (TB) caused by Mycobacterium tuberculosis is an opportunistic infection that affects the lungs in humans. Caseload of TB has been deemed it endemic in various regions of the world and India is on top of that list. The Government of India has set out a goal to eliminate tuberculosis in India by the year 2025 with the help of the National Strategic Plan (NSP) 2017-25. The objective of the index study was to verify the claim of Rajsamand district in Rajasthan, that it witnessed a >20% reduction in TB incidence between 2015 and 2020. Methodology: This was a mixed-methods study. Quantitative component (cross-sectional study): Secondary data review (review of records from Nikshay notification systems and National tuberculosis elimination program (NTEP) reports, utilization of drugs in the public sector, and drug sales in the private sector). Primary data collection through survey. Qualitative component: nominal group technique and key informant interviews. Result: Percentage decline of a ≥ 20% incidence in 2020 compared to baseline 2015 was not seen. The number needed to test (increased by 18.26% in 2020 as compared to the baseline of 2015. TB Score of Rajsamand district for the year 2020 was 68.34 out of 100. Conclusion: Rajsamand district's claim of ≥20% reduction in TB incidence in the year 2020, was rejected.